ACUTE PANCREATITIS: CURRENT UNDERSTANDING OF DEVELOPMENT, DIAGNOSIS, AND TREATMENT - VALERIY I. Podoluzhnyi (Фундаментальная и клиническая медицина)
Here I discuss the recent data on epidemiology, development, diagnosis, and treatment of acute pancreatitis, with the particular focus on its complications. A two-fold increase in incidence of acute pancreatitis has been registered in Kemerovo Region during the recent 24 years. Pancreatic hypertension caused by cholelithiasis or alcohol abuse induces local inflammation and necrosis, with the further spread to the retroperitoneal tissue and abdominal organs if untreated. I also describe the diagnostic algorithm, conservative treatment, low invasive techniques, and laparotomy in management of both sterile and infected pancreatic necrosis. The lecture is intended for gastroenterologists, surgeons, and senior students of medical schools.